Observations on the Intestate Widows Acts, Ireland - Smith, George H. (Statistical and Social Inquiry Society of Ireland, 1879)
Surprise has frequently been expressed at the fact that so little practical result has followed from the passing of the Acts of 36 & 37 Vic. c. 52, and 38 & 39 Vic. c. 27, and that the persons for whose benefit these enactments were introduced and sanctioned have to a very slight extent indeed availed themselves of their provisions. The main purpose sought to be accomplished by these measures? popularly known as the ?Intestate Widows Acts? ?was to enable the property of individuals in the humblest rank to be placed in train for distribution, at an expense bearing some relation to the financial condition of the parties concerned, and to the extent of the assets to be dealt with; but unhappily this commendable intention has been frustrated by the defects of the provisions of the Acts themselves. As a consequence, the number of cases annually dealt with under these statutes throughout Ireland has never exceeded 26 out of a total of about 400, which, except for the complications involved in the procedure, might have been carried out at small cost to needy and deserving litigants.
Read before the Society, 6 May 1979
Keywords: Inheritance law; Succession; Irish Intestate Widows Acts; Irish family law; 314.15